Taste processing in Drosophila larvae - Apostolopoulou, Anthi A. (Front Integr Neurosci, 2015)
The sense of taste allows animals to detect chemical substances in their environment to initiate appropriate behaviors: to find food or a mate, to avoid hostile environments and predators. Drosophila larvae are a promising model organism to study gustation. Their simple nervous system triggers stereotypic behavioral responses, and the coding of taste can be studied by genetic tools at the single cell level. This review briefly summarizes recent progress on how taste information is sensed and processed by larval cephalic and pharyngeal sense organs. The focus lies on several studies, which revealed cellular and molecular mechanisms required to process sugar, salt, and bitter substances.